ARCHAEOLOGY OF THE MIDDLE MAYO RIVER BASIN, MOYOBAMBA, SAN MARTIN - van Dalen Luna, Pieter (2013)
We present the results of the research conducted in the middle basin of the Mayo river, Moyobamba district, department of San Martin. Its a region that has had different cultural periods socio-political developments in other Andean and Amazonian. Its location between the department of Amazonas and the Amazon low (Tarapoto and Loreto), has been a point of transit in the interactions occurring between the two regions, amalgamated by a complex trade network. From research conducted in 2008 and 2009 identified a total of 25 archaeological sites, sites composed mostly of ceramic dispersion and small enclosures oval plan of Andean influence. The results of these investigations show a greater approach to understanding societies that inhabited these lands before the Spanish invasion.